Secondary batteries and electronic devices

By regulating the composition of the isolation film and electrolyte, the low safety and stability problems of secondary batteries under high-temperature and high-speed charging and discharge are solved, low impedance and high safety performance are achieved, and a number of performance indicators are improved.

CN119542681BActive Publication Date: 2025-04-22NINGDE AMPEREX TECHNOLOGY LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510027324.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-22
Estimated Expiration
2045-01-08

AI Technical Summary

Technical Problem

Existing secondary batteries have low safety and stability problems under high-temperature, high-speed charging and discharge, especially when the battery cell charge and energy density increase, it is difficult to ensure the hot box window and circulation performance of the battery cell.

Method used

By regulating the base film porosity of the isolation film and the inorganic particles Dv99 in the inorganic coating within a specific range, the isolation film has physical and chemical stability. At the same time, the content of propionate propionate in the electrolyte and the mass ratio of lithium difluorosulfonimide are also regulated within a specific range to reduce the self-discharge of the battery under fast charging and improve the cycling performance.

Benefits of technology

It realizes the low impedance and high safety performance of the secondary battery under high-temperature and high-speed charging and discharge, and improves the pass rate of the hot box test, the retention rate of the low-temperature cycle capacity and the anti-overcharge performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542681B_ABST
    Figure CN119542681B_ABST
Patent Text Reader

Abstract

The present application provides a secondary battery and an electronic device. The secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator disposed between the positive electrode sheet and the negative electrode sheet. The separator includes a base film and an inorganic coating located on the opposite surface of the base film. The inorganic coating includes a plurality of inorganic particles. The Dv99 of the inorganic particles is A, in μm. The porosity of the base film is B%, wherein the ratio of B to A, B / A, satisfies: 1.25≤B / A≤40. The electrolyte includes propyl propionate. Based on the total mass of the electrolyte, the mass percentage of propyl propionate is C%, wherein C satisfies: 20≤C≤45. Through the special design of the separator and the control of the content of propyl propionate in the electrolyte, the secondary battery has low impedance and high safety performance under high-temperature and high-rate charge and discharge, and can effectively prevent overcharging and improve the cycle performance of the secondary battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical energy storage, and in particular to a secondary battery and an electronic device including the secondary battery. Background Art

[0002] As a clean energy source, secondary batteries are increasingly widely used because they do not generate waste or pollute the environment during use. With the improvement of the charging performance of secondary batteries, higher requirements are also placed on the safety and stability of secondary batteries. For example, the rapid increase in the charging rate of secondary battery cells and the increase in the energy density of the cells are not conducive to the improvement of the hot box window of the cells (the safe temperature at which the cells can be placed in a hot box for testing after charging without catching fire, exploding or smoking). Therefore, while ensuring the good charging performance of secondary batteries, ensuring the safety and stability of secondary batteries has always been a research hotspot. Summary of the invention

[0003] In view of this, the purpose of the present application is to provide a secondary battery and an electronic device that can have low impedance, high safety performance and prevent overcharging under high-temperature and high-rate charge and discharge.

[0004] In a first aspect, the present application provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet, a separator disposed between the positive electrode sheet and the negative electrode sheet, and an electrolyte, wherein the separator comprises a base film and an inorganic coating located on at least one surface of the base film, wherein the inorganic coating comprises a plurality of inorganic particles, wherein the Dv99 of the inorganic particles is A, in units of μm, and the porosity of the base film is B%, wherein the ratio of B to A (B / A) satisfies: 1.25≤B / A≤40;

[0005] The electrolyte includes propyl propionate, and based on the total mass of the electrolyte, the mass percentage of the propyl propionate is C%, wherein C satisfies: 20≤C≤45.

[0006] The present application regulates the porosity of the base film of the isolation membrane and the Dv99 of the inorganic particles in the inorganic coating within a specific range, so that the isolation membrane has a certain stability. The first aspect is the physical stability of the isolation membrane. The isolation membrane can better resist the deformation of the isolation membrane caused by the expansion of the battery core electrode material during the cycle, and when the porosity and the Dv99 of the inorganic particles meet this range, it can well relieve the stress caused by the expansion of the electrode material and resist the attack of gas molecules generated by the side reaction of the electrolyte. The second aspect can also improve the chemical stability of the isolation membrane, that is, at high temperature and high current density, resist the corrosion of the electrolyte to the isolation membrane structure. When the content of propyl propionate in the electrolyte is limited to meet the scope of this application, the side reaction of the electrolyte can be reduced, and the self-discharge of the battery under fast charging can be reduced. The content range of propyl propionate is conducive to maintaining the structural strength of the inorganic particles, and has a certain adaptability and synergistic effect on the isolation membrane that meets the parameters of the application range, and jointly improves the performance of the secondary battery, such as the fast charging voltage drop, the hot box test pass rate and the capacity retention rate of 400 cycles at minus 15°C.

[0007] In combination with the first aspect, in some embodiments, C satisfies: 30≤C≤40. When the range of C meets the range defined in this application, the fast charge resistance change rate and fast charge voltage drop of the secondary battery can be reduced, and the hot box test pass rate and low temperature cycle capacity retention rate of the secondary battery can be improved.

[0008] In some embodiments, A satisfies: 1≤A≤8, and B satisfies: 10≤B≤40. When the ranges of A and B meet the ranges defined in this application, the fast charge resistance change rate and fast charge voltage drop of the secondary battery can be reduced, and the hot box test pass rate and low temperature cycle capacity retention rate of the secondary battery can be improved.

[0009] In some embodiments, the ratio B / A satisfies: 3≤B / A≤35. When the range of B / A satisfies the range defined in the present application, the fast charge resistance change rate and fast charge voltage drop of the secondary battery can be effectively reduced, and the hot box test pass rate and low temperature cycle capacity retention rate of the secondary battery can be improved.

[0010] In some embodiments, A satisfies: 1≤A≤5, and B satisfies: 15≤B≤35. When the ranges of A and B further meet the ranges defined in the present application, the fast charge resistance change rate and fast charge voltage drop of the secondary battery can be more effectively reduced, and the hot box test pass rate and low temperature cycle capacity retention rate of the secondary battery can be improved.

[0011] In some embodiments, the electrolyte further includes lithium bis(fluorosulfonyl)imide, and the mass percentage of the lithium bis(fluorosulfonyl)imide is D% based on the total mass of the electrolyte, wherein the ratio C / D of C to D satisfies: 100≤C / D≤225. When the range of C / D further satisfies the range defined in the present application, the fast charge resistance change rate and fast charge voltage drop of the secondary battery can be more effectively reduced, and the hot box test pass rate and low temperature cycle capacity retention rate of the secondary battery can be improved.

[0012] The present application adjusts the mass ratio of propyl propionate and lithium bis(fluorosulfonyl)imide in the electrolyte to meet a specific range, so that lithium bis(fluorosulfonyl)imide has better dispersibility in the battery, thereby making lithium ions have better ion transmission effect, improving the battery's cycle performance and safety performance. When the ratio is too large, it will lead to excessive propyl propionate content, the viscosity of the electrolyte will increase, thereby reducing the ion transmission effect; when the ratio is too small, lithium bis(fluorosulfonyl)imide cannot be well solvated in propyl propionate, which will cause ion transmission to be delayed. A ratio that is too large or too small will cause the battery effect to deteriorate, such as the fast charging voltage drop, the hot box test pass rate, and the capacity retention rate of 400 cycles at minus 15°C. All of them are significantly reduced.

[0013] In some embodiments, the ratio C / D satisfies: 150≤C / D≤200.

[0014] In some embodiments, the electrolyte further comprises ethylene carbonate and ethyl propionate, and based on the total mass of the electrolyte, the mass percentage of ethylene carbonate is E%, and the mass percentage of ethyl propionate is F%, wherein the ratio of E to F (E / F) satisfies: 0.3≤E / F≤6.

[0015] In the electrolyte of the present application, ethylene carbonate and ethyl propionate have a certain synergistic effect. By regulating the mass ratio of ethylene carbonate and ethyl propionate within a specific range, the formation of side reactions of the electrolyte can be reduced, thereby reducing the self-discharge phenomenon of the battery under fast charging, and improving the cycle performance and safety performance of the battery.

[0016] In some embodiments, the sum of E and F, E+F, satisfies: 20≤E+F≤45.

[0017] By adjusting the total mass percentage of ethylene carbonate and ethyl propionate to 20%-45%, the formation of side reactions in the electrolyte can be further reduced, thereby reducing the self-discharge of the battery under fast charging and improving the cycle performance and safety performance of the battery.

[0018] In some embodiments, the inorganic particles are aluminum oxide or boehmite particles. In the scanning electron microscope image of the isolation membrane, in the area of ​​12.5 μm×10 μm, the mass percentage of aluminum element is measured to be G%, and G satisfies: 25≤G≤50.

[0019] In some embodiments, the ratio A / G of Dv99 to G of the inorganic particles satisfies: 0.02≤A / G≤0.2.

[0020] By regulating the distribution of inorganic particles on the isolation membrane to meet appropriate conditions, the isolation membrane has further strength, structure and chemical stability, which can inhibit the deformation of the battery during high-temperature charging and discharging, thereby improving the battery's cycle performance and safety performance.

[0021] In some embodiments, the isolation film further includes an organic coating, the organic coating is located on a surface of at least one of the inorganic coatings away from the base film, and the organic coating includes a polymer having a melting point of 110-130° C.

[0022] By further providing an organic coating in the isolation membrane and the organic coating comprising a polymer in a specific melting point range, combined with the specific Dv99 range of the inorganic particles of the inorganic coating of the isolation membrane and the specific content of propyl propionate in the electrolyte, the interface between the isolation membrane and the electrolyte has higher chemical stability, and there is a certain structural stability synergistic effect at high temperatures among the three, thereby improving the cycle performance and safety performance of the battery.

[0023] In some embodiments, the isolation film has an average static value less than or equal to 1150V when tested after being left to stand at 80° C. for one hour.

[0024] The isolation film has a low static value and has good stability and self-discharge performance.

[0025] In some embodiments, the positive electrode sheet includes a convex point, the height of the convex point is H, the unit is μm, and the surface density of the positive electrode sheet is I, the unit is mg / cm 2 , where the difference HI between H and I satisfies: -18≤HI≤75.

[0026] Such a setting can well release the stress between materials during the expansion of the secondary battery. At the same time, the bumps can better leave space for embedding of some inorganic particles. When the electrolyte inevitably causes a certain displacement of the inorganic particles during the circulation process, the design of the bumps can reduce the possibility of accumulation of inorganic particles in local areas, thereby improving the cycle performance and safety performance of the battery. For example, the pass rate of the battery's overcharge protection test is increased to 85% or above, the capacity retention rate of the 55°C cycle test for 300 cycles is above 80%, and the retention rate of the float charge test for 200 cycles is above 83%, and the amount of storage gas generated at 60°C does not exceed 9μL.

[0027] In some embodiments, the electrolyte further includes lithium difluorophosphate, and the mass percentage of the lithium difluorophosphate is 0.02%-0.8% based on the total mass of the electrolyte.

[0028] In some embodiments, the electrolyte further includes sodium allyl sulfonate, and the mass percentage of the sodium allyl sulfonate is 0.5%-3% based on the total mass of the electrolyte.

[0029] In a second aspect, the present application provides an electronic device, comprising the secondary battery described in the first aspect. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is a schematic structural diagram of a secondary battery according to one embodiment of the present application.

[0031] Figure 2 It is a schematic diagram of the cross-sectional structure of an isolation membrane according to one embodiment of the present application.

[0032] Description of main component symbols:

[0033] Separator 10 , base film 11 , inorganic coating 13 , organic coating 15 , positive electrode sheet 20 , negative electrode sheet 30 . DETAILED DESCRIPTION

[0034] The embodiments of the present application will be described in detail below. The embodiments of the present application should not be interpreted as limiting the present application.

[0035] As used in this application, the terms "including," "containing," and "comprising" are used in their open, non-limiting sense.

[0036] In addition, sometimes amounts, ratios and other numerical values ​​are presented in range format herein. It should be understood that such range format is for convenience and brevity, and should be flexibly understood to include not only the numerical values ​​explicitly specified as range limits, but also all individual numerical values ​​or sub-ranges encompassed within the range, as if each numerical value and sub-range were explicitly specified.

[0037] In the detailed description and claims, a list of items connected by the terms "one or more of," "one or more of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A or B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, or C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.

[0038] like Figure 1 As shown, the secondary battery provided in the embodiment of the present application includes a separator 10, a positive electrode sheet 20, a negative electrode sheet 30 and an electrolyte. The separator 10 is arranged between the positive electrode sheet 20 and the negative electrode sheet 30 to isolate the positive electrode sheet 20 from the negative electrode sheet 30. The electrolyte penetrates into the porous separator 10. The electrolyte plays a role of conducting ions between the positive electrode sheet 20 and the negative electrode sheet 30.

[0039] In some embodiments, the secondary battery is a lithium-ion battery, but the present application is not limited thereto.

[0040] Isolation film

[0041] In this application, if Figure 2 As shown, the isolation film 10 includes a base film 11 and an inorganic coating layer 13 located on two opposite surfaces of the base film 11 .

[0042] The inorganic coating 13 includes a plurality of inorganic particles. In some embodiments, the Dv99 of the inorganic particles is A, in μm. The base film 11 is a porous structure, and the porosity of the base film 11 is B%, wherein the ratio of B to A B / A satisfies: 1.25≤B / A≤40. For example, B / A can be 1.25, 3, 6, 10, 12, 15, 18, 20, 22, 25, 28, 30, 33, 36, 40 or a range consisting of any two of them.

[0043] Dv99 refers to the particle size corresponding to when the cumulative particle size distribution percentage of the inorganic particles reaches 99%. Porosity refers to the percentage of the pore volume in the base film 11 to the total volume of the base film 11 in the natural state.

[0044] Furthermore, in some embodiments, B / A satisfies: 3≤B / A≤35.

[0045] In some embodiments, the material of the base film 11 is selected from at least one of polyethylene, polypropylene, polyvinylidene fluoride, polyethylene terephthalate, polyimide and aramid. For example, polyethylene includes at least one selected from high-density polyethylene, low-density polyethylene and ultra-high molecular weight polyethylene.

[0046] In some embodiments, the inorganic particles are selected from at least one of aluminum oxide (Al2O3), silicon oxide (SiO2), magnesium oxide (MgO), titanium oxide (TiO2), hafnium dioxide (HfO2), tin oxide (SnO2), cerium dioxide (CeO2), nickel oxide (NiO), zinc oxide (ZnO), calcium oxide (CaO), zirconium oxide (ZrO2), yttrium oxide (Y2O3), silicon carbide (SiC), boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide and barium sulfate.

[0047] The inorganic coating 13 may further include a binder. The binder is selected from at least one of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polyvinyl ether, polytetrafluoroethylene or polyhexafluoropropylene. The inorganic coating 11 can improve the heat resistance, oxidation resistance and electrolyte wetting performance of the isolation membrane 10, and enhance the adhesion between the isolation membrane and the pole piece.

[0048] In some embodiments, the Dv99 of the inorganic particles is 1-8 μm, further 1-5 μm. That is, A satisfies: 1≤A≤8. For example, A can be 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8 or a range consisting of any two thereof. Further, A satisfies: 1≤A≤5.

[0049] In some embodiments, the porosity of the base film 11 is 10%-40%, and further 15%-35%. That is, B satisfies: 10≤B≤40. For example, B can be 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40 or a range consisting of any two of them. Further, in some embodiments, B satisfies: 15≤B≤35.

[0050] By regulating the porosity of the base film of the isolation membrane and the Dv99 of the inorganic particles of the inorganic coating within a specific range, the isolation membrane has a certain stability. The first aspect is the physical stability of the isolation membrane. The isolation membrane can better resist the deformation of the isolation membrane caused by the expansion of the battery cell electrode material during the cycle, and when the porosity and the Dv99 of the inorganic particles meet the range, it can well alleviate the stress caused by the expansion of the electrode material and resist the attack of gas molecules generated by the side reaction of the electrolyte. The second aspect can also improve the chemical stability of the isolation membrane, that is, resist the corrosion of the isolation membrane structure by the electrolyte at high temperature and high current density.

[0051] In some embodiments of the present application, the inorganic particles are aluminum oxide or boehmite particles. In the scanning electron microscope image of the isolation film 10, in the area of ​​12.5 μm×10 μm, the mass percentage of aluminum element is measured to be G%. In some embodiments, the mass percentage of aluminum element is 25%-50%, that is, G satisfies: 25≤G≤50. For example, G can be 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50 or a range consisting of any two of them.

[0052] In some embodiments, the ratio of Dv99 to G of the inorganic particles A / G satisfies: 0.02≤A / G≤0.2. For example, A / G can be 0.02, 0.03, 0.04, 0.05, 0.06, 0.08, 0.1, 0.12, 1, 0.12, 0.14, 0.15, 0.17, 0.19, 0.2, or a range consisting of any two of them.

[0053] By regulating the distribution of inorganic particles on the isolation membrane to meet appropriate conditions, the isolation membrane has further strength, structure and chemical stability, which can inhibit the deformation of the battery during high-temperature charging and discharging, thereby improving the battery's cycle performance and safety performance.

[0054] In some embodiments, such as Figure 2 As shown, the isolation film 10 further includes an organic coating 15, which is located on the surface of the inorganic coating 13 away from the base film 11. The organic coating 15 can be disposed on only one side of the base film 11, or on both sides of the base film 11. Figure 2 As shown, the organic coating 15 is provided on both sides of the base film 11 .

[0055] The organic coating 15 contains a polymer having a melting point of 110-130° C. The polymer can be selected from at least one of polypropylene, poly-4-methylpentene, polytetrafluoroethylene, polyvinylidene fluoride and cycloolefin copolymers. The organic coating 15 can increase the melting point of the separator 10, improve the strength and high temperature performance of the secondary battery.

[0056] By further providing an organic coating in the isolation membrane and the organic coating comprising a polymer in a specific melting point range, combined with the specific Dv99 range of the inorganic particles of the inorganic coating of the isolation membrane and the specific content of propyl propionate in the electrolyte, the interface between the isolation membrane and the electrolyte has higher chemical stability, and there is a certain structural stability synergistic effect at high temperatures among the three, thereby improving the cycle performance and safety performance of the battery.

[0057] In some embodiments, after the isolation film 10 is left at a temperature of 80° C. for one hour, the average static value thereof is tested to be less than or equal to 1400V. The static value is obtained by testing with KEYENCE SK-H050. The static value of a group of isolation films (including multiple isolation films) can be tested, and the average static value of the multiple isolation films can be calculated. The isolation film has a lower static value, good stability and self-discharge performance.

[0058] In some embodiments, the thickness of the inorganic coating 13 may be 1.5-2.1 μm, for example, 1.8 μm. The thickness of the organic coating 15 may be 2.5-5 μm, for example, 3 μm.

[0059] In some embodiments, the thickness of the isolation film 10 as a whole is in a range of about 3 μm to 480 μm.

[0060] Electrolyte

[0061] The electrolyte generally includes an electrolyte salt and a solvent. In the present application, the solvent of the electrolyte includes propyl propionate. Based on the total mass of the electrolyte, the mass percentage of propyl propionate is C%. In some embodiments, based on the total mass of the electrolyte, the mass percentage of propyl propionate is 20%-45%. That is, C satisfies: 20≤C≤45. For example, C can be 20, 23, 25, 28, 30, 32, 35, 38, 40, 43, 45 or a range consisting of any two of them.

[0062] Further, in some embodiments, based on the total mass of the electrolyte, the mass percentage of propyl propionate is 30%-40%, that is, C satisfies: 30≤C≤40.

[0063] By further regulating the propyl propionate content in the electrolyte within a specific range, the side reactions of the electrolyte can be reduced and the self-discharge of the battery under fast charging can be reduced. The propyl propionate content range is beneficial to maintaining the structural strength of the inorganic particle material of the inorganic coating of the isolation membrane, and has a certain adaptability and synergistic effect on the isolation membrane that meets the parameters of the application range, and jointly improves the performance of the secondary battery, such as the fast charging voltage drop, the hot box test pass rate and the capacity retention rate after 400 cycles at minus 15°C.

[0064] Further, in some embodiments of the present application, the electrolyte salt of the electrolyte includes lithium bis(fluorosulfonyl)imide (LiFSI). Based on the total mass of the electrolyte, the mass percentage of lithium bis(fluorosulfonyl)imide is D%, wherein the mass ratio C / D of propyl propionate to lithium bis(fluorosulfonyl)imide satisfies: 5≤C / D≤225. For example, C / D can be 5, 15, 25, 35, 30, 45, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 225 or a range consisting of any two of them.

[0065] The present application adjusts the mass ratio of propyl propionate to lithium bis(fluorosulfonyl)imide in the electrolyte to meet a specific range, so that lithium bis(fluorosulfonyl)imide has better dispersibility in the battery, thereby making lithium ions have better ion transmission effect, improving the battery's cycle performance and safety performance. When the ratio is too large, it will lead to excessive propyl propionate content, the viscosity of the electrolyte will increase, and thus reduce the ion transmission effect; when the ratio is too small, lithium bis(fluorosulfonyl)imide cannot be well solvated in propyl propionate, which will cause ion transmission to be delayed. A ratio that is too large or too small will cause the battery effect to deteriorate.

[0066] In some embodiments, based on the total mass of the electrolyte, the mass percentage of lithium bis(fluorosulfonyl)imide is 0.2%-5%, further 0.2%-1.5%. That is, 0.2≤D≤5, further, 0.2≤D≤1.5. For example, D can be 0.2, 0.5, 0.8, 1, 1.2, 1.5, 1.7, 2, 2.2, 2.5, 2.8, 3, 3.3, 3.5, 3.8, 4, 4.2, 4.5, 4.8, 5 or a range consisting of any two of them.

[0067] Furthermore, in some embodiments, C / D satisfies: 13.3≤C / D≤225.

[0068] In some embodiments, the electrolyte further includes additives of ethylene carbonate and ethyl propionate, and based on the total mass of the electrolyte, the mass percentage of ethylene carbonate is E%, and the mass percentage of ethyl propionate is F%, wherein the mass ratio E / F of ethylene carbonate and ethyl propionate satisfies: 0.3≤E / F≤6.

[0069] There is a certain synergistic effect between ethylene carbonate and ethyl propionate. By regulating the mass ratio of ethylene carbonate and ethyl propionate within a specific range, the formation of side reactions in the electrolyte can be reduced, thereby reducing the self-discharge of the battery under fast charging and improving the cycle performance and safety performance of the battery.

[0070] In some embodiments, based on the total mass of the electrolyte, the mass percentage of ethylene carbonate is 10%-30%, further 15%-25%. That is, 10≤E≤30, further 15≤E≤25. For example, E can be 10, 13, 15, 20, 23, 25, 28, 30 or a range consisting of any two of them.

[0071] In some embodiments, based on the total mass of the electrolyte, the mass percentage of ethyl propionate is 5%-30%, further 5%-20%. That is, 5≤F≤30, further 5≤F≤20. For example, F can be 5, 8, 10, 13, 15, 18, 20, 23, 25, 30 or a range consisting of any two of them.

[0072] In some embodiments, based on the total mass of the electrolyte, the mass percentage of the sum of ethylene carbonate and ethyl propionate is 20%-45%, and the sum of E and F, E+F, satisfies: 20≤E+F≤45. For example, E+F can be 20, 25, 27, 30, 35, 40, 45, or a range consisting of any two of them.

[0073] By adjusting the mass percentage of the total of ethylene carbonate and ethyl propionate to 20%-45%, the formation of side reactions in the electrolyte can be further reduced, thereby reducing the self-discharge of the battery under fast charging and improving the cycle performance and safety performance of the battery.

[0074] In some embodiments of the present application, the electrolyte further comprises lithium difluorophosphate. Based on the total mass of the electrolyte, the mass percentage of lithium difluorophosphate is 0.02%-0.8%.

[0075] In some embodiments of the present application, the electrolyte further comprises sodium allyl sulfonate. Based on the total mass of the electrolyte, the mass percentage of sodium allyl sulfonate is 0.5%-3%.

[0076] In some embodiments, the additives included in the electrolyte may also include vinyl sulfate (DTD), vinylene sulfate (VC), 1,3-propane sultone, and may further include fluoromethyl methyl carbonate, difluoromethyl methyl carbonate, trifluoromethyl methyl carbonate, trifluoroethyl methyl carbonate or bis(trifluoroethyl) carbonate.

[0077] In some embodiments, in addition to LiFSI, the electrolyte also includes an ionizable lithium salt, and the ionizable lithium salt includes at least one of LiPF6, LiSbF6, LiAsF6, LiClO4, LiN(C2F5SO2)2, CF3SO3Li, LiC(CF3SO2)3 or LiC4BO8. The concentration of the ionizable lithium salt in the electrolyte is not particularly limited, preferably 0.5 mol / L or more, more preferably 0.8 mol / L or more, and further preferably 1.0 mol / L or more. In addition, it is preferably 3 mol / L or less, more preferably 2 mol / L or less, and further preferably 1.7 mol / L or less. If the concentration of these ionizable lithium salts is too low, it may cause the number of mobile lithium ions in the electrolyte to be insufficient. On the other hand, if the concentration of these ionizable lithium salts is too high, it may cause the viscosity of the electrolyte to increase, resulting in an increase in the impedance of the electrolyte, which reduces the migration rate of lithium ions, and thus may cause the performance of the electrochemical device to decrease.

[0078] In some embodiments, the electrolyte further comprises at least one of fluoroether, fluoroethylene carbonate and ether solvents. In some embodiments, the electrolyte further comprises a non-aqueous solvent. The non-aqueous solvent may be a carbonate compound, a carboxylate compound, an ether compound, other organic solvents or a combination thereof.

[0079] The carbonate compound may include not only a chain carbonate compound, but also a cyclic carbonate compound, a fluorinated carbonate compound or a combination thereof.

[0080] In addition to diethyl carbonate (DEC) defined in the present application, examples of the chain carbonate compound may include ethyl propionate (EP), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC) and combinations thereof. Examples of the cyclic carbonate compound are ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinyl ethylene carbonate (VEC) or combinations thereof. Examples of the fluorinated carbonate compound are fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, trifluoromethylethylene carbonate, or a combination thereof.

[0081] Examples of the carboxylic acid ester compound are methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanolide, valerolactone, mevalonolactone, caprolactone, methyl formate, or a combination thereof.

[0082] Examples of the ether compound are dibutyl ether, tetraglyme, diglyme, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, or a combination thereof.

[0083] Examples of other organic solvents in the electrolyte are dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate, and phosphoric acid esters or combinations thereof.

[0084] The secondary battery of the present application mainly has low impedance and high safety performance under high-temperature and high-rate charge and discharge, and can effectively prevent overcharging, mainly through the special design of the isolation membrane and the regulation and design of the electrolyte formula.

[0085] Positive electrode

[0086] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector. The positive electrode active material layer may be located on one side or both sides of the positive electrode current collector.

[0087] The positive electrode active material layer is usually rolled to reduce the gaps between the positive electrode material particles and make them more closely arranged. After rolling, convex points are formed on the positive electrode sheet. The height of the convex point is H, in μm. The surface density of the positive electrode sheet is I, in mg / cm 2 In some embodiments, the difference HI between the height H of the bump and the surface density I of the positive electrode sheet satisfies: -18≤HI≤75. For example, HI can be -18, -10, -7, 0, 5, 10, 15, 20, 30, 40, 50, 60, 70, 75, or a range consisting of any two of them.

[0088] Such a setting can well release the stress between materials during the expansion of the secondary battery. At the same time, the bumps can better leave space for embedding of some inorganic particles. When the electrolyte inevitably causes a certain displacement of the inorganic particles during the circulation process, the design of the bumps can reduce the possibility of accumulation of inorganic particles in local areas, thereby improving the cycle performance and safety performance of the battery. For example, the pass rate of the battery's overcharge protection test is increased to 85% or above, the capacity retention rate of the 55°C cycle test for 300 cycles is above 80%, and the retention rate of the float charge test for 200 cycles is above 83%, and the amount of storage gas generated at 60°C does not exceed 9μL.

[0089] In some embodiments, the height of the bump is 10-80 μm, that is, 10≤H≤80. For example, H can be 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80 or a range consisting of any two thereof.

[0090] In some embodiments, the surface density of the positive electrode sheet is 5-28 mg / cm 2 That is, 5≤I≤28. For example, I can be 5, 7, 10, 13, 15, 17, 20, 23, 25, 28 or a range consisting of any two of them.

[0091] In some embodiments, the positive electrode current collector may be made of aluminum foil. Of course, other positive electrode current collectors commonly used in the art may also be used. In some embodiments, the thickness of the positive electrode current collector may be 1 μm to 200 μm. In some embodiments, the positive electrode active material layer may be coated only on a partial area of ​​the positive electrode current collector. In some embodiments, the thickness of the positive electrode active material layer may be 20 μm to 490 μm, and further preferably, the thickness may be 20 μm to 400 μm, and further, it may be 40 μm to 120 μm, and further, it may be 40 μm to 90 μm.

[0092] In some embodiments, as described above, the positive electrode active material layer includes a positive electrode active material. In some embodiments, the positive electrode active material may include at least one of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, or lithium nickel manganese oxide, and the above positive electrode active materials may be doped and / or coated. Further preferably, the positive electrode active material is lithium cobalt oxide or lithium iron phosphate.

[0093] In some embodiments, the positive electrode active material layer also includes a positive electrode binder and a positive electrode conductor. In some embodiments, the positive electrode binder may include polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, styrene-acrylate copolymer, styrene-butadiene copolymer, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinyl acetate, polyvinylpyrrolidone, polyvinyl ether, polytetrafluoroethylene or polyhexafluoropropylene. In some embodiments, the positive electrode conductor may include at least one of conductive carbon black, acetylene black, Ketjen black, graphene, carbon nanotubes or carbon fibers.

[0094] Negative electrode

[0095] In some embodiments, the negative electrode plate may include a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector. The negative electrode active material layer may be disposed on one side or both sides of the negative electrode current collector. In some embodiments, the negative electrode current collector may be at least one of copper foil, nickel foil, or a carbon-based current collector. In some embodiments, the thickness of the negative electrode current collector may be 1 μm to 200 μm. In some embodiments, the negative electrode active material layer may be coated only on a partial area of ​​the negative electrode current collector. In some embodiments, the thickness of the negative electrode active material layer may be 10 μm to 500 μm. It should be understood that these are exemplary only and other suitable thicknesses may be used.

[0096] In some embodiments, as described above, the negative electrode active material layer includes a negative electrode active material. In some embodiments, the negative electrode active material includes at least one of natural graphite, artificial graphite, or a silicon-based material. In some embodiments, the silicon-based material includes at least one of silicon, a silicon-oxygen compound, a silicon-carbon compound, or a silicon alloy.

[0097] In some embodiments, the negative electrode active material layer may also include a negative electrode conductor and / or a negative electrode binder. The negative electrode conductor may include at least one of carbon black, acetylene black, Ketjen black, graphene, carbon nanotubes, or carbon fibers. In some embodiments, the negative electrode binder may include at least one of carboxymethyl cellulose (CMC), polyacrylic acid, polyacrylic acid salt, polyacrylic acid ester, polyvinyl pyrrolidone, polyimide, polysiloxane, or styrene-butadiene rubber. It should be understood that the materials disclosed above are only exemplary, and the negative electrode active material layer may be any other suitable material. In some embodiments, the mass ratio of the negative electrode active material, the negative electrode conductor, and the negative electrode binder in the negative electrode active material layer may be (80~99): (0.5~10): (0.5~10), and it should be understood that this is only exemplary and not intended to limit the present application.

[0098] In some embodiments of the present application, taking lithium-ion batteries as an example, the positive electrode sheet, the isolation membrane, and the negative electrode sheet are wound or stacked in sequence to form an electrode assembly, and then placed in a shell such as an aluminum-plastic film for packaging, and the electrolyte is injected, formed, and packaged to make a lithium-ion battery.

[0099] The embodiment of the present application also provides an electronic device including the above-mentioned secondary battery. The electronic device of the embodiment of the present application is not particularly limited, and it can be any electronic device known in the prior art. In some embodiments, the electronic device can include, but is not limited to, a notebook computer, a pen input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, a liquid crystal television, a portable cleaner, a portable CD player, a mini disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium ion capacitor, etc.

[0100] Some specific embodiments and comparative examples are listed below to better illustrate the present application, and both the embodiments and comparative examples use lithium-ion batteries as examples.

[0101] Preparation of lithium-ion batteries

[0102] <Example 1-1>

[0103] Positive electrode: The positive electrode active material is lithium cobalt oxide LiCoO2 (BET: 0.3m 2 / g), conductive agent Super-P, binder polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 97:1:2, N-methylpyrrolidone (NMP) was added, and an acrylate-containing additive (2800ppm) was added. The mixture was stirred evenly under the action of a vacuum mixer to obtain a positive electrode slurry with a solid content of 65wt%. The positive electrode slurry was evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 12μm, and the aluminum foil was dried at 120℃ for 1h to obtain a positive electrode active material layer with a thickness of 90μm and a surface density of 25mg / cm 2 Repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode sheet coated with a positive electrode active material layer on both sides. Then, after cold pressing, cutting, and welding the pole ears, it is dried under vacuum conditions at 120°C for 1 hour to obtain a positive electrode sheet with a size of 74mm (width) × 854mm (length) and a current collector empty foil area at the tail. The height of the surface convex point of the positive electrode sheet is 30μm.

[0104] Alumina (Dv99 is 0.7μm) and binder PVDF are mixed in a mass ratio of 80:20, N-methylpyrrolidone (NMP) is added, and the mixture is stirred evenly under the action of a vacuum mixer to obtain an inorganic coating slurry with a solid content of 30wt%. The inorganic coating slurry is first evenly coated on one surface of the positive current collector aluminum foil at the tail of the above-mentioned positive electrode plate (this surface is defined as the a surface, and the other surface of the current collector is defined as the b surface), and dried at 120°C for 1h to obtain a positive electrode plate with an inorganic coating on one surface of the current collector, i.e., the a surface, the length of the inorganic coating is 95mm, and the thickness of the inorganic coating is 2.5μm.

[0105] Negative electrode: Weigh 100 g of negative electrode active material (artificial graphite with a particle size of 11 μm), 1 g of conductive agent (carbon black), and 4 g of binder (styrene-butadiene rubber, SBR) and add them to 3 g of N-methylpyrrolidone and 120 g of water to form a negative electrode slurry. The negative electrode slurry is stirred, coated on the negative electrode collector, dried, roll-pressed, and spot-welded to the electrode ear to obtain the battery negative electrode.

[0106] Electrolyte: In a glove box filled with argon, EC (ethylene carbonate) was first heated at a high temperature of 60°C to convert it into a liquid state, and then a solvent was prepared with a mass ratio of EC (ethylene carbonate): DMC (dimethyl carbonate): EMC (ethyl methyl carbonate) = 1:1:1, propyl propionate, ethyl propionate and fluoroethylene carbonate were added, and then solid lithium hexafluorophosphate was added to prepare a 1.1 mol / L lithium hexafluorophosphate solution by a constant volume method, and solid LiFSI accounting for 0.3% of the total mass of the electrolyte was added, lithium difluorophosphate and sodium allyl sulfonate were added, and finally adiponitrile and 1,3,6- Hexanetricarbonitrile, such that the mass content of adiponitrile accounts for 3.6% of the total mass of the entire electrolyte, the mass content of 1,3,6-hexanetricarbonitrile accounts for 2% of the total mass of the entire electrolyte, fluoroethylene carbonate accounts for 1% of the total mass of the electrolyte, propyl propionate accounts for 35% of the total mass of the electrolyte, the mass of lithium bis(fluorosulfonyl)imide accounts for 0.2% of the total mass of the entire electrolyte, the mass of ethylene carbonate accounts for 20% of the total mass of the entire electrolyte, the mass of ethyl propionate accounts for 10% of the total mass of the entire electrolyte, the mass of lithium difluorophosphate accounts for 0.1% of the total mass of the electrolyte, and the mass of sodium allyl sulfonate accounts for 0.5% of the total mass of the entire electrolyte.

[0107] Separator membrane: A 10 μm thick polyethylene (PE) microporous membrane with a porosity of 35% was selected as the base membrane of the separator membrane.

[0108] Inorganic coating of isolation membrane: Inorganic particle boehmite with a Dv50 of 0.5µm and a Dv99 of 1µm was mixed with polyacrylate in a mass ratio of 88:12 and dissolved in deionized water to form an inorganic coating slurry with a solid content of 43%. The obtained inorganic coating slurry was then uniformly coated on one side of the PE base film by a micro-concave coating method to obtain an inorganic coating, which was dried in an oven. The thickness of the inorganic coating was 1.8μm.

[0109] Preparation of organic coating of isolation membrane: Add the first polymer polyethylene as the base monomer polymer (melting point of 110°C) particles into the stirrer and stir evenly; add sodium carboxymethyl cellulose into the stirrer and stir evenly; add dimethyl siloxane, a wetting agent, into the stirrer, then add deionized water and stir, adjust the viscosity of the slurry to 45mPa•s and the solid content to 6%, and obtain an organic coating slurry. The organic coating slurry is applied to the inorganic coating on one side of the base film by stripe coating, so that the distance between adjacent bonding points is 120μm, and after drying in an oven, an organic coating is obtained. The thickness of the organic coating is 3μm. The mass ratio of the first polymer, sodium carboxymethyl cellulose, and dimethyl siloxane is 95:0.5:4.5. Among them, the polymer is spherical or quasi-spherical in the isolation membrane, and the sphericity R of the polymer satisfies 0.7≤R≤1.0.

[0110] Preparation of the inorganic coating on the other side of the isolation membrane: Inorganic particle boehmite with a Dv50 of 0.5µm and a Dv99 of 1µm was mixed with polyacrylate in a mass ratio of 88:12 and dissolved in deionized water to form an inorganic coating slurry with a solid content of 47%. The obtained inorganic coating slurry was then evenly coated on the other side of the PE base film by a micro-concave coating method to obtain a heat-resistant layer, which was dried in an oven. The thickness of the inorganic coating was 1.8μm.

[0111] Preparation of the oil-based porous coating on the other side of the isolation membrane: Inorganic boehmite particles and binder polyvinylidene fluoride are mixed at a volume ratio of 1.4, and then N-methylpyrrolidone (first solvent) is added and stirred evenly to obtain a coating liquid, wherein the solid content of the coating liquid is 8%; the coating liquid is coated on the porous substrate (polyethylene) by dip coating to form a wet film; the porous substrate (polyethylene) with the wet film is immersed in a coagulation liquid containing deionized water (third solvent) and N-methylpyrrolidone (NMP, second solvent) for phase inversion, wherein the mass percentage of N-methylpyrrolidone (second solvent) in the coagulation liquid is 38%, and the temperature of the coating liquid and the coagulation liquid is 25°C; after being immersed in the coagulation liquid for 30s, it is placed in an oven and dried at 60°C to obtain an isolation membrane with a porous film. Scanning electron microscopy was used to test the mass percentage of aluminum element in the area of ​​12.5μm×10μm, which can be calculated to be 50%.

[0112] Preparation of negative electrode sheet: artificial graphite, conductive carbon black, styrene-butadiene rubber (SBR), and carboxymethyl cellulose sodium (CMC) are mixed at a weight ratio of 96.5:1.5:1:1, deionized water is added, and the mixture is stirred evenly under the action of a vacuum mixer to obtain a negative electrode slurry, wherein the solid content of the negative electrode slurry is 75wt%. The negative electrode slurry is evenly coated on one side of the negative electrode current collector copper foil, and dried at 120°C to obtain a negative electrode sheet coated with a negative electrode active material layer with a thickness of 90μm on one side, and the above steps are repeated on the other side of the negative electrode current collector copper foil to obtain a negative electrode sheet coated with a negative electrode active material layer on both sides, and then after cold pressing, cutting, and slitting, a negative electrode sheet with a specification of 476mm×93.5mm is obtained.

[0113] Preparation of lithium-ion batteries: stack the positive electrode sheet, separator, and negative electrode sheet in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and wind them to obtain an electrode assembly. After welding the pole ears, place the electrode assembly in an outer packaging aluminum-plastic film, remove moisture at 80°C, inject the above-mentioned electrolyte, and obtain a lithium-ion battery through vacuum packaging, standing, formation, shaping, capacity testing and other processes.

[0114] <Example 1-2 to Example 1-34>

[0115] The preparation of the lithium-ion batteries of Examples 1-2 to 1-34, the preparation of the isolation membrane, electrolyte, positive electrode sheet, and negative electrode sheet are basically the same as the preparation steps of Example 1-1. The differences are shown in Tables 1-1 and 1-2 below.

[0116] <Comparative Examples 1-1 to 1-7>

[0117] The preparation of the lithium-ion batteries of Comparative Examples 1-1 to Comparative Examples 1-7, the preparation of the isolation membrane, electrolyte, positive electrode sheet, and negative electrode sheet are basically the same as the preparation steps of Example 1-1, and the differences are shown in Table 1-2 below.

[0118] <Example 2-1 to Example 2-41>

[0119] The preparation of the lithium-ion batteries of Examples 2-1 to 2-41, the preparation of the isolation membrane, the electrolyte, the positive electrode sheet, and the negative electrode sheet are basically the same as the preparation steps of Example 1-1. The differences are shown in Tables 2-1 and 2-2 below.

[0120] The test method is as follows:

[0121] (I) Capacity retention test of 200 intermittent cycles at -15°C:

[0122] At -15°C, the lithium-ion battery was allowed to stand for 30 minutes; it was charged to 4.45V at a constant current rate of 0.5C, and charged to 0.05C at a constant voltage rate of 4.45V; the battery was allowed to stand in a -15°C environment for 24 hours; the battery was cross-current discharged to 3.0V at a rate of 0.5C, and the battery discharge capacity was recorded; this was a complete intermittent charge and discharge cycle, and the battery was charged and discharged 150 times in the same way.

[0123] Capacity retention rate (%) of lithium ion battery after 150th cycle = discharge capacity at 150th cycle / first discharge capacity×100%.

[0124] (II) Capacity storage test after 300 cycles at 55°C

[0125] At 25°C, the lithium-ion battery is charged at a constant current of 1C to a voltage of 4.45V, then charged at a constant voltage of 4.45V to a current of 0.05C, and then discharged at a current density of 0.5C to 3V. The initial discharge capacity of the lithium-ion battery is tested as C0; then the lithium-ion battery is placed in a constant temperature box at 55°C, charged to 4.45V at a current density of 1C, and then discharged to 2.8V at 0.5C, and a cycle test is performed for 299 cycles. After the test, the discharge capacity at the 300th cycle is recorded as C1;

[0126] The capacity retention rate (%) of a lithium-ion battery after 300 cycles stored at 45°C for 10 days = (C1 / C0) × 100%.

[0127] (III) Electrolyte component test:

[0128] The electrolyte components were tested by GC-MS and combined with the external standard method.

[0129] (IV) 140℃ hot box test pass rate:

[0130] Step 1: Charge the prepared battery at a constant current of 0.5C to a cut-off voltage of 4.2V, then charge at a constant voltage to a cut-off current of 200mA, and then let it stand for 5 minutes;

[0131] Step 2: Attach the temperature-sensing wire to the fully charged battery between the two tabs, connect the two tabs to monitor the voltage, and hang the battery cell vertically in the box;

[0132] Step 3: Heat the heat box to 145°C at a rate of 5°C and maintain for 60 minutes.

[0133] Judging criteria: The battery passes if it does not catch fire or explode. Count the number of batteries that pass the hot box test.

[0134] (V) Fast charging voltage drop test:

[0135] At 25°C, charge the lithium-ion battery at 3C constant current to 4.45V, then charge at 4.45V constant voltage to 0.05C, and then discharge at 1C constant current to 3.0V. Let stand for 5 minutes, then test the voltage, which is recorded as the voltage before storage. Then store at -20°C for 24 hours, re-test the voltage, which is recorded as the voltage after storage. Voltage drop = voltage before storage - voltage after storage.

[0136] (VI) Fast charging 200 cycles resistance change rate test:

[0137] At 30°C, the prepared lithium-ion battery was left to stand for 6 hours, and then the initial electrochemical impedance value was measured by the EIS electrochemical impedance method. The lithium-ion battery was then charged at a constant current of 0.5C to a voltage of 4.45V, and then charged at a constant voltage of 4.45V to a current of 0.05C, and then discharged at a current density of 0.5C to 3V. The electrochemical impedance R2 of the 200th cycle was tested after 200 cycles. The rate of change was calculated as follows: [(R2-R1) / R1]×100%

[0138] (VII) Overcharge prevention test pass rate:

[0139] At 50°C, the discharged battery cell is charged at a constant current of 3.5C to 5.0V, then changed to constant voltage charging. The charging time is limited to 6 hours or the charging is stopped when the battery surface temperature is stable (temperature difference within 30 minutes ≤ 2°C). Judgment standard: The battery cell does not catch fire. Each embodiment is tested with 20 parallel samples as a group.

[0140] (VIII) 60℃ storage gas generation test:

[0141] At 60°C, the battery was cycled 20 times at a rate of 1C with a test voltage of 2.0V-4.45V. A battery gas production test device was used to detect the gas production after the battery cycle.

[0142] (IX) Float charge test retention rate:

[0143] Place the lithium-ion battery in a 25℃ constant temperature box and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature. Charge with a constant current of 1C to a voltage of 4.45V, charge with a constant voltage to a current of 0.05C, and then discharge with a constant current of 1C to a voltage of 3.0V, and record the discharge capacity as the initial capacity of the lithium-ion battery. Then charge with a constant current of 0.5C to a voltage of 4.45V, charge with a constant voltage to a current of 0.05C, transfer the test lithium-ion battery to a 45℃ constant temperature box, and then charge with a constant voltage of 4.45V to the 199th cycle, then transfer the battery to a 25℃ constant temperature box, let it stand for 60 minutes, discharge with a constant current of 1C to a voltage of 3.0V, and record the discharge capacity of the 199th cycle as the discharge capacity of the lithium-ion battery after storage. Then charge with a constant current of 1C to a voltage of 4.45V, charge with a constant voltage to a current of 0.05C, and then discharge with a constant current of 1C to 3.0V, and record the discharge capacity as the recoverable capacity of the lithium-ion battery;

[0144] Capacity retention rate after 200 cycles of floating charge = (initial discharge capacity-recoverable capacity) / initial discharge capacity×100%.

[0145] Table 1-1

[0146]

[0147] Table 1-2

[0148]

[0149] According to the test results in Tables 1-1 and 1-2, compared with Comparative Examples 1-1 to 1-7, the fast charging 200-cycle resistance change rate of Examples 1-1 to 1-34 is lower than that of Comparative Examples 1-1 to 1-7, and the fast charging voltage drop, hot box test pass rate and capacity retention rate of 400 cycles at -15°C of Examples 1-1 to 1-34 are significantly improved, which means that by adjusting B / A to meet: 1.25≤B / A≤40B / A and C to meet: 20≤C≤45, the fast charging resistance change rate can be effectively reduced, and the fast charging voltage drop, hot box test pass rate and capacity retention rate of 400 cycles at -15°C can be improved.

[0150] Table 2-1

[0151]

[0152] Table 2-2

[0153]

[0154] According to the test results in Tables 2-1 and 2-2, by regulating the A / G of the isolation membrane to satisfy: 0.02≤A / G≤0.2, and the HI of the positive electrode to satisfy: -18≤HI≤75, the overcharge test pass rate of the lithium-ion battery can be effectively controlled to reach 85% or above, the capacity retention rate of 300 cycles at 55°C can be above 80%, and the retention rate of 200 cycles of floating charge can be above 83%, and the amount of storage gas generated at 60°C does not exceed 9μL.

[0155] It should be noted that the above are only specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application; the implementation methods of the present application and the features in the implementation methods can be combined with each other without conflict. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.

Claims

1. A secondary battery, comprising a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator disposed between the positive electrode sheet and the negative electrode sheet, characterized in that: The isolation film includes a base film and an inorganic coating located on the opposite surface of the base film, the inorganic coating includes a plurality of inorganic particles, the Dv99 of the inorganic particles is A, in μm, the porosity of the base film is B%, wherein the ratio of B to A (B / A) satisfies: 1.25≤B / A≤40; The electrolyte includes propyl propionate, and based on the total mass of the electrolyte, the mass percentage of the propyl propionate is C%, wherein C satisfies: 20≤C≤45; The isolation film includes a base film, and the base film is sandwiched between two inorganic coating layers; The inorganic particles are selected from at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide and barium sulfate.

2. The secondary battery according to claim 1, characterized in that: C satisfies: 30≤C≤40.

3. The secondary battery according to claim 1, characterized in that: A satisfies: 1≤A≤8, B satisfies: 10≤B≤40.

4. The secondary battery according to claim 1, characterized in that The ratio B / A satisfies: 3≤B / A≤35.

5. The secondary battery according to claim 4, characterized in that A satisfies: 1≤A≤5, B satisfies: 15≤B≤35.

6. The secondary battery according to claim 1, characterized in that The electrolyte further includes lithium bis(fluorosulfonyl)imide, and the mass percentage of the lithium bis(fluorosulfonyl)imide is D% based on the total mass of the electrolyte, wherein a ratio C / D of C to D satisfies: 100≤C / D≤225.

7. The secondary battery according to claim 6, characterized in that: The ratio C / D satisfies: 150≤C / D≤200.

8. The secondary battery according to claim 1, characterized in that The electrolyte further comprises ethylene carbonate and ethyl propionate. Based on the total mass of the electrolyte, the mass percentage of ethylene carbonate is E%, and the mass percentage of ethyl propionate is F%, wherein a ratio E / F of E to F satisfies: 0.3≤E / F≤6.

9. The secondary battery according to claim 8, characterized in that: The sum of E and F, E+F, satisfies: 20≤E+F≤45.

10. The secondary battery according to claim 1, characterized in that: The inorganic particles are aluminum oxide or boehmite particles. In the scanning electron microscope image of the isolation membrane, in the area of ​​12.5 μm×10 μm, the mass percentage of aluminum element is measured to be G%, wherein G satisfies: 25≤G≤50.

11. The secondary battery according to claim 10, characterized in that: The ratio of A to G, A / G, satisfies: 0.02≤A / G≤0.

2.

12. The secondary battery according to claim 1, characterized in that: The isolation film further includes an organic coating, which is located on a surface of at least one of the inorganic coatings away from the base film, and the organic coating includes a polymer with a melting point of 110-130° C.

13. The secondary battery according to claim 1, characterized in that: The average static value of the isolation film after being left to stand at 80° C. for one hour is less than or equal to 1150V.

14. The secondary battery according to claim 1, characterized in that: The positive electrode sheet includes a convex point, the height of the convex point is H, the unit is μm, and the surface density of the positive electrode sheet is I, the unit is mg / cm 2 , where the difference HI between H and I satisfies: -18≤HI≤75.

15. The secondary battery according to claim 1, characterized in that: The electrolyte also includes lithium difluorophosphate. Based on the total mass of the electrolyte, the mass percentage of the lithium difluorophosphate is 0.02%-0.8%.

16. The secondary battery according to claim 1, characterized in that: The electrolyte further comprises sodium allyl sulfonate, and the mass percentage of the sodium allyl sulfonate is 0.5%-3% based on the total mass of the electrolyte.

17. An electronic device, characterized in that: A secondary battery comprising any one of claims 1 to 16.

Citation Information

Patent Citations

  • Isolating membrane and preparation method thereof, secondary battery and preparation method thereof, and power utilization device

    CN119029492A

  • Electrolyte, electrochemical device and electronic device

    CN119170869A